Prospects of researching Georgian Tales - Tagauri, Gabriel (Actual Problems of Kartvelology, 2019)
Present paper analyses conceptual and structural characteristics of Georgian tales, including those controversial aspects that still call for solution. All thirty-one functions fairy-tails, formulated by V.Y. Propp, are more of a universal nature than purely national. However, as long as every tale integrates national features into narration, the purpose of my research was to explore how the conventional intents of a tail transform and how general motives of its storyline get modified in the national context. Particularly important was to understand how the national basis gets reflected in the texts of Georgian folk and literary tales. Authors of the folk and literary pieces alike are very selective in what words they put into the mouths of their caracters so that their spoken language would accurately communicate the message that the authors aspired to get across. Present paper is inspired by the these throughts and aspirations.